PEREMPUAN MUSLIM FAK-FAK: KEKERASAN DALAM RUMAH TANGGA DAN PROSES PERDAMAIAN - Cahyo Pamungkas (Jurnal Masyarakat dan Budaya, 2009)
This paper is adressed to answer how the Papua Moslem Women of Fak-Fak overcome domestic violence. Refering to Marx and Engel, such violence rooted in a domination in the field of economics or in a capitalist mode of production as a continuation of class domination in the history of human being. Based on empirical data, it is found that structural factors such as economic condition contributes to the violence through economic pressures that being faced by poor families. Beside that, cultural factors also is acknowledged to cause violence through modernization, which reduced local cultural values. However, the violence can not be related to the local tradition of Bahamata people of Fak-Fak since the tradition respects and acknowledges the role of Women in their family and structure of tribe. To overcome the violence, some of Moslem women organization has campaigned and socialized of anti-domestic violence issues although it is still artificial.